2015
DOI: 10.1007/s10815-015-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the promoter region of interleukin-10 gene increases the risk for spontaneous abortions—a triad study

Abstract: Purpose Spontaneous abortion or miscarriage is the natural death of an embryo or foetus in the early stages of prenatal development. Interleukin-10 is an anti-inflammatory cytokine, produced by human cytotrophoblasts, and defects in its production result in specific pathological conditions during pregnancy. The present study is aimed to evaluate the association of IL-10 -1082G/A polymorphism in spontaneous abortions by comparing foetal, maternal and paternal groups-a triad study. Methods A total of 50 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…37 The studies analyzed identified changes in pro-inflammatory cytokines such as IL-1β, IL-18 13,16,17,38,39 and IL-10, which can have an anti-inflammatory or pro-inflammatory effect. 37,40 Another contribution of the immune system in spontaneous abortion is referred to as a response, in which Human Leukocyte Antigens (HLA) stimulate the maternal immune system against the presence of the fetus. 41 Regarding genetic changes, the polymorphisms of the vascular endothelial growth factor -VEGF stand out (this being an important factor in the regulation of fetal and placental angiogenesis), 8,42 VEGF 43 receptor polymorphism and growth factor polymorphism similar to insulin-2 -IGF-2 (main fetal-placental growth factor that stimulates trophoblast invasion and growth).…”
Section: Discussionmentioning
confidence: 99%
“…37 The studies analyzed identified changes in pro-inflammatory cytokines such as IL-1β, IL-18 13,16,17,38,39 and IL-10, which can have an anti-inflammatory or pro-inflammatory effect. 37,40 Another contribution of the immune system in spontaneous abortion is referred to as a response, in which Human Leukocyte Antigens (HLA) stimulate the maternal immune system against the presence of the fetus. 41 Regarding genetic changes, the polymorphisms of the vascular endothelial growth factor -VEGF stand out (this being an important factor in the regulation of fetal and placental angiogenesis), 8,42 VEGF 43 receptor polymorphism and growth factor polymorphism similar to insulin-2 -IGF-2 (main fetal-placental growth factor that stimulates trophoblast invasion and growth).…”
Section: Discussionmentioning
confidence: 99%
“…The −1082A/G (rs1800896) polymorphism of the IL-10 gene's promoter region has been extensively studied due to its reported involvement in the abnormal expression of IL-10 in RM. [ 21 61 63 64 65 66 67 68 ] It has also been revealed by a study conducted on a hypertensive rat model that IL-10 contributes to the normalisation of blood pressure and endothelial function. These results highlight the significance of this cytokine in a healthy pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 58 ] In addition, our results were also supported by the findings of several studies. [ 64 65 66 ] A meta-analysis by Peng et al . found a significant association between −1082A/G polymorphism and RM risk, and they also concluded that G allele, as well as the GG genotype, increased the risk.…”
Section: Discussionmentioning
confidence: 99%